Pain assessment, cognitive and cortical changes with full mouth rehabilitation in a group of children - Nancy Mohamed Metwally; Osama Abd Allah Ragab; Mostafa Shaaban Husseiny Kandil; Lamis Ahmed Elghareb (BMC Oral Health, 2024)
Abstract Background A change in professionals’ perspectives on the value of general anesthesia (GA) for pediatric patients, including those with disabilities, medical conditions, severe oral issues, and challenging behaviors. Full-mouth rehabilitation under GA allows for the comprehensive treatment of all oral health problems in a single visit, without requiring the child’s active participation. Extensive dental problems are often associated with severe dental pain, which can impact cognitive function, including perception, attention, memory, reasoning, language, communication, and executive functions. Individuals experiencing pain tend to perform less optimally cognitively. Aim This study aimed to investigate changes in cognition, brain function, and cortical alterations in children who underwent extensive dental rehabilitation under GA. Patients andMethods Thirty uncooperative, healthy children aged 6–12 with extensive dental issues were enrolled. Pain levels were assessed using the FLACC and WBFPS scales before treatment, one week after, and three months later. Cognitive assessments, including the WCST, processing speed, digit span, and Trail Making Test, as well as EEG measurements, were also performed. Results The results showed a significant improvement in pain levels reported by the children or their caregivers after the dental procedures, both at one week and three months. All cognitive measures, such as digit span, processing speed, and WCST performance, demonstrated substantial improvements after the treatment. The Trail Making Test also exhibited statistically significant variations before and after the dental procedures. Additionally, the MOCA test revealed a notable improvement in cognitive skills following the treatment. Furthermore, the EEG power ratio, an indicator of changes in the power balance within each frequency band, showed a statistically significant difference after the dental procedures. Conclusion the findings of this study suggest that full-mouth rehabilitation under GA can lead to improved pain management, as well as enhanced cognitive and brain functions in children. Future perspectives More clinical studies with a longer follow-up period and a different age range of children are required to investigate the connection between brain function and oral rehabilitation involving restorations or occlusion issues.